Yep. . Show your work and box in your answers. Solve for r.. Use this, it gets the job done.
x
Click to expand

Comments(197):

[ 197 comments ]
What do you think? Give us your opinion. Anonymous comments allowed.
#6 - neocortex (09/13/2012) [+] (16 replies)
This image has expired
Use this, it gets the job done.
User avatar #21 - lupislord (09/13/2012) [+] (2 replies)
I just solved the equation...

...then i remembered...

...I'm here to procrastinate from my math homework....
#20 - jayloonar (09/13/2012) [-]
MFW simple quadratic
MFW simple quadratic
#129 - alexclement (09/13/2012) [+] (1 reply)
x^2+6x+9 = x+3
-3 -x -3

x^2+5x+6 = 0
(x+3) (x+2) = 0

x = -3
x = -2

HUEHUEHUE
#160 - drmrniceguy (09/14/2012) [-]
mfw the entirety of threads down there are trying to solve this simple algebra equation.
#72 - PedoBearsAcomin (09/13/2012) [+] (8 replies)
Are people seriously showing of and working it out, this is like kid maths
Are people seriously showing of and working it out, this is like kid maths
#77 - SweetJesus (09/13/2012) [-]
>mfw i haven't even used math like this for 3 years now
User avatar #2 - lillelise (09/13/2012) [+] (1 reply)
Good one, but X is also = -3 and -2
User avatar #156 - thekingofangmar (09/14/2012) [+] (3 replies)
I deduced that the answer is in fact x= -6/7, due to the fact the first term is x multiplied by 2, not x^2.
#148 - dantastic (09/14/2012) [-]
MFW x2 = x^2
#31 - sbfiredragon (09/13/2012) [+] (2 replies)
Assuming this is in fact a quadratic equation (as that is the only way I have found to complete this sum) I do believe this is the answer according to my calculations.
x2+6x+9=x+3
x2+5x+6=0
(x+2)(x+3)
x+2=0 x+3=0
x=-2 x=-3
User avatar #135 - MysticTomatoe (09/14/2012) [+] (3 replies)
When you get to calculus, this is like 1+1 in difficulty
#16 - Absolute Madman (09/13/2012) [+] (7 replies)
x2 + 6x + 9 = x + 3

(x+3)(x+3) = (x+3)

1(x+3) = 1

x + 3 = 1

x = -2
User avatar #24 to #16 - bboywakear (09/13/2012) [-]
(x+3)(x+3) = (x+3)

**** logic
User avatar #168 - higaphix (09/14/2012) [+] (1 reply)
most people settle at x = -2 or -3
its actually -2 if you replug it into the equation.
#173 to #168 - pineapplepeople (09/14/2012) [-]
It's both.
User avatar #81 - Psychotic (09/13/2012) [+] (18 replies)
x^2+6x+9=x+3
(x+3)*(x+3)=(x+3)
(x+3)=1
x=-2
User avatar #84 to #81 - micota (09/13/2012) [-]
You did that wrong... x=-2 and x=-3
x^2+6x+9=x+3
x^2+5x+6=0
(x+3)*(x+2)=0
x=-3 and -2
-4
#89 - decayingapple has deleted their comment [+] (3 replies)
#118 to #89 - parasiticpsycho (09/13/2012) [-]
here have the correct one
#207 - breakfastlunch (09/14/2012) [+] (1 reply)
x^2 + 6x + 9 = x + 3
x^2 + 5x + 6 = 0
(x + 3) (x + 2) = 0
x = -3. -2

Really isn't hard enough to warrant blackmail
User avatar #58 - kolsinder ONLINE (09/13/2012) [+] (7 replies)
(x+2)(x+3). Took about 30 seconds.
User avatar #60 to #58 - midclassmonkey (09/13/2012) [-]
x = -2 x = -3 , now it is solved for x
#177 - ibangbabys (09/14/2012) [-]
MFW math
#171 - loneranger ONLINE (09/14/2012) [+] (3 replies)
MFW I see all this math...
#185 to #181 - mahaiz (09/14/2012) [-]
Comment Picture
[ 197 comments ]
Leave a comment
 Friends (0)